A prospective "bottom up" study of the costs of faecal incontinence in ambulatory patients. Issue 5 (14th May 2018) - Patton, Vicki; Parkin, Katrina; Moore, Kate H.
Abstract : Background and Aim: The few studies that have examined direct costs of faecal incontinence are limited in that they employed retrospective databases, postal surveys, and focused upon institutionalised patients or post partum women. The aim of the current study was to identify the direct pre‐treatment costs of faecal incontinence expended by a range of home dwelling patients and identify relationships between costs and severity of incontinence. Methods: Consecutive patients attending an outpatient clinic for treatment of faecal incontinence were interviewed using a questionnaire, modeled on the Dowel Bryant Incontinence Cost Index. The information collected included costs of: (i) basic personal hygiene: pads, laundry, wipes, cleansers; (ii) medication: loperamide, creams and stool bulking agents; and (iii) diagnostic: medical attendance, anorectal physiology, colonoscopy. Costs were broken down into personal expenses, government costs, and costs to health funds. A St Mark's Faecal Incontinence Severity Score was recorded. Results: A total of 100 consecutive patients consented (15 males, 85 females) mean age 70.8 (SD12) years. Mean St Mark's score was 12 (SD4.5). The median total patient cost was 437.72 AUD (range 0‐2807) per annum. Government costs were 537AUD (range 135‐1657), and health fund median 0 AUD (0‐1628). Incontinence severity correlated with personal expense only median 283.75AUD (range 0‐2350). The aged were more incontinent but costs did not increase in relation to age. Conclusion: Faecal incontinence results in a substantial financial burden for both patients and Government. Effective treatments which relieve the financial burden of faecal incontinence, are likely to be economically advantageous into the future for both patients and Government.